Efficacy and safety of eszopiclone combined with drug therapy in the treatment of insomnia after stroke: A network meta-analysis and systematic review. - Ruo-Yang Li; De-Liang Zhu; Ke-Yu Chen (PLoS ONE, 2024)
Objective To evaluate the efficacy and safety of multi-drug therapy based on eszopiclone in the treatment of insomnia after stroke using a network meta-analysis method and to provide evidence for clinical practice. Method Computer searches of PubMed, Excerpt Medica Database (Embase), Cochrane Library Central Register of Controlled Trials, APA PsycInfo, CNKI, WanFang, Sinomed and other databases were performed to search for clinical randomized controlled studies (RCTs) on multi-drug therapy based on eszopiclone in the treatment of insomnia patients after stroke. The search time was from the establishment of each database until July 2023. The bias risk assessment tool recommended by Cochrane was used to evaluate the quality of the included RCTs. Stata 14.0 was applied to perform network meta-analysis using Review Manager 5.3 software for traditional meta-analysis. Result Eighteen RCTs and 1646 patients were ultimately included, involving 11 treatment options. The results of the network meta-analysis showed that the ranking of Pittsburgh Sleep Quality Index (PSQI) decline was eszopiclone combined with sweet dream oral liquid (ESZ+SDOL)>eszopiclone combined with a shugan jieyu capsule (ESZ+SGJYC)>eszopiclone combined with agomelatine (ESZ+AGO)>eszopiclone combined with flupentixol and melitracen tablets (ESZ+FMT)>eszopiclone combined with yangxue qingnao granules (ESZ+YXQNG)>eszopiclone combined with mirtazapine (ESZ+MIR)>ESZ>FMT; the modified Edinburgh Scandinavia Stroke Scale (MESSS) decline ranking was ESZ+SDOL>ESZ+AGO>ESZ; and the clinical total effective rate ranking was eszopiclone combined with a xuefu zhuyu capsule (ESZ+XFZYC)>ESZ+MIR>ESZ+SGJYC>ESZ+SDOL> ESZ+FMT>ESZ+YXQNG>ESZ>FMT. In terms of clinical adverse reactions, in addition to ESZ therapy, ESZ+ESC had the highest number of adverse reactions, with abdominal pain being the most common. ESZ+YXQNG had the most types of adverse reactions, with 8 types. Conclusion Multi-drug therapy based on eszopiclone can effectively improve the sleep quality of patients with insomnia after stroke, and ESZ+SDOL has significant efficacy and safety. However, due to the limitations of this study, efficacy ranking cannot fully explain the superiority or inferiority of clinical efficacy. In the future, more multicentre, large sample, double-blind randomized controlled trials are needed to supplement and demonstrate the results of this study.